Woody structure facilitates invasion of woody plants by providing perches for birds. Issue 19 (3rd September 2017) - Prather, Chelse M.; Huynh, Andrew; Pennings, Steven C.
Abstract: Woody encroachment threatens prairie ecosystems globally, and thus understanding the mechanisms that facilitate woody encroachment is of critical importance. Coastal tallgrass prairies along the Gulf Coast of the US are currently threatened by the spread of several species of woody plants. We studied a coastal tallgrass prairie in Texas, USA, to determine if existing woody structure increased the supply of seeds from woody plants via dispersal by birds. Specifically, we determined if (i) more seedlings of an invasive tree ( Tridacia sebifera ) are present surrounding a native woody plant ( Myrica cerifera ); (ii) wooden perches increase the quantity of seeds dispersed to a grassland; and (iii) perches alter the composition of the seed rain seasonally in prairie habitats with differing amounts of native and invasive woody vegetation, both underneath and away from artificial wooden perches. More T. sebifera seedlings were found within M. cerifera patches than in graminoid‐dominated areas. Although perches did not affect the total number of seeds, perches changed the composition of seed rain to be less dominated by grasses and forbs. Specifically, 20–30 times as many seeds of two invasive species of woody plants were found underneath perches independent of background vegetation, especially during months when seed rain was highest. These results suggest that existing woody structure in a grassland can promote further woody encroachment by enhancing seed dispersal by birds. This finding argues for management to reduce woody plant abundance before exotic plants set seeds and argues against the use of artificial perches as a restoration technique in grasslands threatened by woody species. Abstract : Woody encroachment threatens prairie ecosystems globally, and thus understanding the mechanisms that facilitate woody encroachment are of critical importance. To determine if existing woody structure increased the delivery of woody plant seeds, we quantified seed rain in prairie habitats with differing amounts of native and invasive woody vegetation over time, both underneath and away from artificial wooden perches. Our results suggest that existing woody structure in a grassland may promote further woody encroachment by enhancing seed dispersal by birds; this finding argues for management to reduce woody plant abundance before exotic plants set seeds and argues against the use of artificial perches as a restoration technique in grasslands threatened by woody species.